Irigasi Kolonial di Lumbung Padi Nasional: Analisis Nilai Penting dan Rekomendasi Pemanfaatan Bagi Pendidikan - Syahruddin Mansyur; Nur Ihsan Djindar; Asmunandar nfn; M Nur; Hamdan Hamado (Balai Arkeologi Provinsi Sulawesi Utara, 2022)
Bendung Benteng in Pinrang Regency is agricultural irrigation that has been operating since the colonial era and is a key factor in increasing rice production in South Sulawesi. This paper aims to identify the significance value of the cultural resources of Bendung Benteng and formulate appropriate policy recommendations for optimizing utilization, especially in the realm of education. The method used is a literature review, interviews, and archaeological observation, descriptive analysis by sorting information that can sow the significance and importance of the Bendung Benteng. The results of the analysis show that the Bendung Benteng as an archaeological resource has historical, scientific, and character education values. This important value also shows the value of sustainability that can connect the past, present, and future. Therefore, the Bendung Benteng is seen as a heritage that must be preserved and sustainable, so it needs to be immediately designated as a Cultural Heritage. Cross-sectoral cooperation is also needed to establish various programs, including forms of socialization to raise interest and awareness to preserve water heritage management; also, the determination of Bendung Benteng Irrigation as a Joint Field Laboratory for related fields.